Paying Off Debt or Forgiving Debt? Semantic and Intertextual Analysis on Lord’s Prayer in Smith-Van Dyck Arabic Bible Translation - Yuangga Kurnia Yahya; Siti Nikmatul Rochma; Umi Mahmudah (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2024)
The Smith and Van Dyck Arabic Bible Translation, which first appeared in 1865, is the most widely used translation in the Christian Arab community. The expressions that appear in the translation have some quite striking differences with other Arabic translations of the Bible. This research will focus on one of the messages in Lord's Prayer, specifically Matthew 6:12 about prayer for forgiveness and forgiveness to others which has different diction from the Jesuit Arabic Bible of 1881. This study will use a post-colonialism perspective in Bible studies through semantic and intertextual analysis. This research concluded two main things. First, the quality of the SVD Bible translation from English to Arabic, as seen in Matthew 6:12 has a low level of accuracy and legibility. This can be seen from the choice of words "نغفر” as well as the use of verbs in the future form for source language texts that use the past tense. Second, the results of the SVD Bible translation also provide an overview of Western Christian ideology, which is quite dominant. The representation of this is the choice of the word "sin" rather than "debt", because debt is not a problem in a capitalist lifestyle. In fact, this mindset normalizes the existence of debt to meet the needs of human life. This shows that the translation movement carried out in the 19th century AD became one of the media for spreading the ideas of capitalism and colonialism to various colonial areas.